Mednarodnopravno upravičenje države do odškodnine za stroške sprejema migrantov - Krajnc, Marko (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2018)
Massive migration flows nowadays represent a huge financial burden for many states and the question arises as to whether host countries may obtain under international law a compensation from countries of origin for the costs relating to admission of people who were forced to flee therefrom. To claim compensation successfully, one first has to establish that people fled from the country of origin as a result of its acts. Then, one has to present a valid ground for the claim for compensation, which is either a violation of the obligation not to cause large-scale flows of forced migrants, which is owed to the host country individually, or violations of human rights as erga omnes partes obligations, which are owed to a certain group of states, including the host country that is specially affected by those violations. Finally, one has to demonstrate the occurrence of actual damage, namely all the costs relating to admission of forced migrants which are of sufficient causal proximity to the wrongful acts of the country of origin, and which the host country cannot avoid.
Keywords: compensation; costs; country of origin; država gostiteljica; država izvora; forced migrants; host country; migranti; odškodnina; stroški